Photodynamics of Subependymal Giant Cell Astrocytoma (SEGA) with 5-Aminolevulinic Acid (5-ALA/Gliolan©). (1st October 2022) - Ghani, Imran; Patel, Sabina; Bodi, Istvan; Vergani, Francesco; Ashkan, Keyoumars; Bhangoo, Ranjeev; Lavrador, Jose Pedro
Abstract: AIMS: 5-ALA (Gliolan©) is a valuable surgical tool used predominantly in high grade tumours, which utilises tissue fluorescence to improve the visualisation of the brain-tumour interface. This ensures safe maximal resection, while preserving healthy brain. While Gliolan© use in low grade tumours has previously been reported with variable results, reports of its use and success in the context of SEGA are extremely rare. This report highlights the use of Gliolan© in a patient presenting with a Subependymal Giant Cell Astrocytoma (in a background of tuberous sclerosis), facilitating maximal safe resection and preserving eloquent tissue. METHOD: Tumour resection was performed with pre-operative DTI-fiber tracking and mapping. A transsulcal minimal invasive parafascicular approach (tsMIPS) was carried out with assistance of NICO BrainPath© tubular retractor system (60x13.5), neuronaviagtion, Gliolan©, intra-operative neuro monitoring (IONM), and ultrasound guidance RESULTS: The tumour was found to have both bright and pale fluorescence in the cystic and solid components respectively. Resection was limited to the soft cystic component only, as the solid tumour component showed anatomical attachment to the subgenual area and the fornix. No fluorescence was perceived at the end of resection. The patient made a good recovery with no post-operative deficits. Histopathology confirmed subependymal giant cell astrocytoma (SEGA, WHO grade I). No adjuvant treatment was required CONCLUSION: This reports suggests 5-ALA may be beneficial in the safe resection of SEGAs. Further studies and technological advances in the area of photodynamics, imaging, and intra-operative mapping may be helpful to fully evaluate the efficacy of 5-ALA in SEGAs and other low-grade tumours.